Dewan Bandaraya Kuala Lumpur (DBKL 1) / Mohammad Hariz Mohd Yunus ... [et al.] - Mohammad Hariz, Mohd Yunus; Wan Azzyati Nabihah, Wan Shahrul Nizam; Siti Suriani, Muhammad; Nurul Syafiqah, Mazlan; Shazana Adila, Ramli (2019)
Dewan Bandaraya Kuala Lumpur (DBKL) is a local authority that center of many socio-economic various activities including business, finance, administration, education, religion, culture and sports. The design concept that have use to DBKL Tower 1 building is Islamic geometric design that symbol represents the nation identity and also expression of Malay Muslim are majority ethnic group in the country. DBKL Tower 1 also provide facilities and services that ease occupants and visitor of the building such as café, kindergarten and cooperative. The classification of maintenance that have been used are preventive maintenance which covers on mechanical and electrical, and corrective maintenance that had been done for small cases. There are use in-house and our-source contractors for maintenance. We learnt that maintenance is very important to create a good rating on building services and building condition.